Assessment of Nurses' Staff Knowledge about Child Physical Maltreatment A Field Study in Some Health Centers in Lattakia City - مصطفى, نسرين; زمزم, سوزان; علي, وعد (Latakia University Journal -Medical Sciences Series, 2022)
Child Physical Maltreatment: CPM is a global health problem, with serious consequences that affect the child's health, development, dignity and society as a whole. The knowledge of nurses in health centers about this problem is an essential pillar in enabling them to exercise their multiple roles in managing it. Therefore, the current descriptive study aimed to identify the knowledge of the nursing staff in health centers about CPM. As their number reached 70 nurses working in 9 health centers in Lattakia city, they were selected using the convenient sample method, and the data were collected using a questionnaire developed by the researcher. The study found that the nurses' knowledge level was moderate about CPM forms, psychological and behavioral indicators, parents and child caregiver indicators of CPM by 69.4%, 53.3% and 61%, respectively, while their knowledge level was weak about physical indicators of CPM by 48.6%. The overall level of their knowledge is moderate at 57.3%. The research did not show a statistically significant relationship between nurses' knowledge and any of their demographic characteristics. The study recommended the need to design an educational program about CPM that is presented periodically to nurses in health centers, and to conduct research on nurses' knowledge about other forms of child maltreatment.